Improving Physical Activity Level on Elderly People by using Transtheoretical Model Approach - Siregar, Rinco; Gultom, Rumondang (Sari Mutiara Indonesia University Press, 2018)
It is important to promote physical activity for elderly people, but to improve the level of physical activity of elderly people is a challenge for health workers. The purpose of this quasi-experimental study was to determine the effect of exercise consultation program by using the Transtheoretical Model (TTM) approach on physical activity level in elderly people at Darussalam’s Community Health Center in 2017. The two comparison groups for this study were purposively designed for pre-test/post-test procedures; sixty elderly people at Darussalam’s Community Health Center with randomly allocated into the experimental (30 people) and the control (30 people) groups. While the experimental group received the exercise consultation for 6 weeks, the control group received routine care. Physical Activity Scale for the Elderly (PASE) was used to assess the physical activity of the elderly. Comparative assessments on differences in the level of physical activity both within the group using Wilcoxson matched-pairs and between group using Mann Withney U Test. The results of this study found that after receiving exercise consultation program, level of physical activity in elderly people significantly increased in the experimental group (p < .05), but there was no significant difference in the control group. Between groups, level of physical activity significantly increased after receiving the exercise consultation while no change was found among those who did not (p <.05). The exercise consultation program by using TTM approach could increase the level of physical activity of elderly people. Implication: Exercise consultation by TTM is a simple intervention could promote the physical activity of elderly people. Suggestion: Health worker can use this intervention to improve the physical exercise of elderly people.